2021
DOI: 10.1080/13533312.2020.1869541
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Peace Agreements and Political Trust in Post-War Guatemala, Nepal, and Northern Ireland

Abstract: Her research interests include popular support for political institutions and peace-building mechanisms, as well as the consequences of political violence on people's attitudes. Her work has been published in journals such as Journal of Conflict Resolution,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…For a more detailed discussion of the conflicts, see Dyrstad et al (2021), but we note here that in all three cases, group inequalities played an important role in fueling the conflict in the first place. In Guatemala and Nepal, the rebels enjoyed support from marginalized groups, including rural indigenous people, lower castes, and ethnic minorities—and, indeed, Guatemala’s rural indigenous population was heavily targeted (Commission for Historical Clarification 1999).…”
Section: Case Selectionmentioning
confidence: 84%
“…For a more detailed discussion of the conflicts, see Dyrstad et al (2021), but we note here that in all three cases, group inequalities played an important role in fueling the conflict in the first place. In Guatemala and Nepal, the rebels enjoyed support from marginalized groups, including rural indigenous people, lower castes, and ethnic minorities—and, indeed, Guatemala’s rural indigenous population was heavily targeted (Commission for Historical Clarification 1999).…”
Section: Case Selectionmentioning
confidence: 84%
“… 30 37 Distrust in the government has been shown to influence public behaviour in the context of major health threats. 37–39 Studies of trust in the COVID-19 vaccine in Latin America found that two of the most common contributors to vaccine hesitancy were distrust of the government and mistrust in the vaccine development process. 10 11 16 40 Mistrust in public health campaigns can lead to higher susceptibility to vaccine misinformation and myths.…”
Section: Introductionmentioning
confidence: 99%
“…The historical legacies and systemic health inequities have engendered distrust in the government and health systems by the Indigenous Maya populations 30 37. Distrust in the government has been shown to influence public behaviour in the context of major health threats 37–39.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field’s lack of knowledge surrounding civilians’ perceptions of whether the government will implement the peace agreement is rather surprising because a growing body of literature that recognizes that civilians’ engagement with and acceptance of peace processes is critical for the sustainability of peace (Haass et al 2022). Indeed, despite the fact that peace agreements are primarily negotiated and ultimately signed by warring parties, how civilians perceive the peace process is central to the transition from war to peace (Dyrstad et al 2021, 607).…”
mentioning
confidence: 99%